Monitoring response and resistance to the novel arsenical darinaparsin in an AML patient - Torsten Holm eNielsen; Nathalie eJohnson; Nicolas eGarnier; Stanley eKwan; Lu eYao; Eftihia eCocolakis; Josée eHébert; Robert A. Morgan; Éric ePaquet; Kevin P. Callahan; Craig T. Jordan; Sarit eAssouline; et al. (Frontiers Media S.A., 2013)
Acute myeloid leukemia (AML) with inversion of chromosome 3 is characterized by overexpression of EVI1 and carries a dismal prognosis. Arsenic-containing compounds have been described to be efficacious in malignancies overexpressing EVI1. Here we describe a case of AML with inv(3)(q21q26.2) treated with the organic arsenical darinaparsin. Using a personalized medicine approach, different arsenicals were screened for anti-leukemic effect against the patient's cells ex vivo. The most promising compound, darinaparsin, was selected for in vivo treatment. Clinical effect was almost immediate, with a normalization of temperature, a stabilization of white blood cell (WBC) counts and an increased quality of life. Longitudinal monitoring of patient response and resistance incorporating significant correlative studies on patient derived blood samples over the two cycles of darinaparsin given to this patient allowed us to evaluate potential mechanisms of response and resistance. The anti-leukemic effects of darinaparsin correlated with inhibition of the alternative NF-κB pathway and production of the inflammatory cytokine IL-8. Emergence of resistance was suspected during treatment cycle 2 and supported by xenograft studies in nude mice. Darinaparsin resistance correlated with an attenuation of the effect of treatment on the alternative NF-κB pathway. The results from this patient indicate that darinaparsin may be a good treatment option for inv(3) AML and that inhibition of the alternative NF-κB pathway may be predictive of response. Longitudinal monitoring of disease response as well as several correlative parameters allowed for the generation of novel correlations and predictors of response to experimental therapy in a heavily pretreated patient.